ENHANCING ESP STUDENTS WRITING SKILL DURING THE COVID-19 PANDEMIC BY USING INSTAGRAM - Kurnia Kurnia; Hamzar Hamzar (ANGLO-SAXON: Jurnal Ilmiah Program Studi Pendidikan Bahasa Inggris, 2021)
The covid 19 pandemic has led the Indonesian government to carry out distant learning. This study aims to give an overview of a potential Instagram platform that can be used in teaching writing for ESP university students during the pandemic. Besides, social media is part of technology advancement to improve students' motivation and the efficacy of learning a language (Nugroho & Rahmawati, 2020). The present study sheds light on the effect of the use of Instagram on ESP students writing ability. The pre-experimental research will be conducted in eight meetings, including the writing pre-test and post-test. The students will be assigned to write a descriptive essay using Instagram as the instructional medium. Moreover, a questionnaire will be given to reveal their perceptions toward the use of Instagram to practice writing. The finding of this study is expected to provide a significant contribution to the realm of English for specific purposes (ESP) teaching in Indonesia.